Fatigue Life Prediction of Tripod Sliding Universal Coupling based on RecurDyn - Zhao Shun; Sun Li; Luo Kaiyang; Liu Xin (Jixie chuandong)
On the basis of kinematics analysis, the rigid-flexible coupling dynamics simulation model of the tripod sliding universal coupling is established by using RecerDyn software. The variation of contact stress of the sliding rod of the transmission element with the parameters such as the angle between the input shaft and the output shaft, rotation frequency and load is analyzed in depth. On this basis, the fatigue life of tripod slip universal coupling is predicted based on the stress time history life calculation criterion. The research results lay a foundation for further analysis of the dynamics characteristics and lubrication characteristics of the tripod sliding universal coupling, and provide a basis for its structural design and application.